Improvement of transient response in grid‐tied photovoltaic systems using virtual inertia. Issue 1 (10th December 2020) - Kumar, Dhivya Sampath; Lau, Preston; Sharma, Anurag; Khambadkone, Ashwin; Srinivasan, Dipti
Abstract: Photovoltaic (PV) generation systems, unlike conventional generators, do not possess any inherent inertia. The problem is further amplified by the fact that they are non‐dispatchable and highly intermittent by nature. Furthermore, the rate at which PV power output changes is of a much shorter timescale than that of conventional generators. Thus, integrating them in large quantities to the power grid without appropriate measures will compromise the power grid stability. One of the feasible solutions is to implement the concept of virtual inertia to PV systems, by adding energy storage systems (ESS) such as batteries in parallel with PV systems. In this paper, the ESS will be controlled to regulate the ramp rate (RR) of the PV power output to the grid, which smoothens the overall generation power profile. By modelling the grid, PV, ESS and load individually in the s‐domain and using an equivalent overall two‐machine, two‐area model, the impact of implementing virtual inertia is demonstrated. The results highlight the effectiveness in using ESS to control the RR and improving the transient responses of the overall grid system. Moreover, the economic impact and feasibility of ESS are also analysed using a residential PV and load profile from Singapore.